2022
DOI: 10.3390/jcm11175084
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Effect and Safety of Nanoliposomal Irinotecan with Fluorouracil and Folinic Acid after Gemcitabine-Based Therapy in Patients with Advanced Pancreatic Cancer: A Multicenter, Prospective Observational Study

Abstract: Although the combination of nanoliposomal irinotecan plus fluorouracil/folinic acid (nal-IRI/FF) exhibited survival benefits in gemcitabine-refractory patients with advanced pancreatic cancer (APC) in the phase III NAPOLI-1 trial, there is limited data on the efficacy and safety of this regimen in real-world settings in Japan. This multicenter, prospective observational study enrolled patients with APC who received nal-IRI/FF after a gemcitabine-based regimen from July 2020 to June 2021. We collected and analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 24 publications
4
6
1
Order By: Relevance
“…These survival outcomes appear inferior to the NAPOLI-1 trial results which showed a median PFS of 3.1 months and a median OS of 6.1 months and to the findings from other studies that included patients with no prior exposure to conventional IRI ( 23 , 25 , 26 ). However, in the present study and similar retrospective studies, nal-IRI was administered mainly as the third-line or later lines of therapy.…”
Section: Discussioncontrasting
confidence: 95%
“…These survival outcomes appear inferior to the NAPOLI-1 trial results which showed a median PFS of 3.1 months and a median OS of 6.1 months and to the findings from other studies that included patients with no prior exposure to conventional IRI ( 23 , 25 , 26 ). However, in the present study and similar retrospective studies, nal-IRI was administered mainly as the third-line or later lines of therapy.…”
Section: Discussioncontrasting
confidence: 95%
“…The safety pro le of NFF in the current study appears acceptable in comparison with that in previous reports [19][20][21][22][23][24][25][26][27][28][29][30]. The incidence rates of grade 3 or 4 AEs were < 30%.…”
Section: Discussionsupporting
confidence: 48%
“…Meanwhile, although grade 3 or 4 anorexia was only observed in 12% of the patients, this rate might still be slightly high. It is possible that the RDIs of nal-IRI and FU were higher than those in other reports [13,30]. Meanwhile, our study cohort included more patients who had undergone prior biliary drainage (26%) compared with the NAPOLI-1 trial cohort (13%) [13].…”
Section: Discussionmentioning
confidence: 99%
“…There are many reports on predictors of treatment-response by nal-IRI-based therapy. In particular, CAR, NLR, GPS, total bilirubin, carcinomatosis, and previous treatment with irinotecan have been significantly associated with overall survival (3)(4)(5)(6)(7)(8). However, no study has reported the risk factors for the adverse events during nal-IRI/FL treatment based on the analysis of factors other than the UGT1A1 polymorphism in clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this trial result, the regulatory agency in Japan has approved the nal-IRI plus 5-FU and L-leucovorin (nal-IRI/FL) combination therapy. Particularly interesting studies focused on predictors of treatment-response by nal-IRI-based therapy in patients with pancreatic cancer have indicated that C-reactive protein/albumin ratio (CAR), neutrophil/lymphocyte ratio (NLR), Glasgow prognostic score (GPS), total bilirubin, carcinomatosis, and previous irinotecan treatment are significantly associated with overall survival (3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 99%